Melatonin enhances stress tolerance in rubber seedlings - Yang, H.; Dai, L., Weia, Y., Deng, Z. and Li, D. (Proceedings of the IRRDB International Rubber Conference 2023, 20-21 February 2023, IRRDB, Kuala Lumpur, Malaysia, pp. 79-92.)
The role of melatonin has been well investigated in animals. However, it$1 (Bs possible function is less clear in plants, especially in rubber trees. This study demonstrate that melatonin acts as a potential agent to enhance salt stress tolerance in rubber seedlings. Chlorophyll degradation and H2O2 accumulation in leaves of seedlings under salinity stress were significantly relieved by melatonin treatment. Transcriptome analysis suggested that melatonin acted as a potential antioxidant. Its exogenous application enhanced antioxidant protection mainly by regulating the genes involved in photosynthesis, ROS metabolism, flavonoids, and melatonin biosynthesis. These results demonstrate that melatonin can enhance salt stress tolerance directly or indirectly by counteracting the cellular accumulation of H2O2 in rubber seedlings. Thus, further investigation on melatonin$1 (Bs roles in stress tolerance will provide new insights on the potential use of this metabolite to mitigate abiotic stresses in rubber trees.s
Keywords: Melatonin; Salinity stress; Antioxidant hydrogen peroxide; Transcriptome; Rubber seedling